2022
DOI: 10.1021/acsabm.2c00292
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatible Amphipathic Carbon Quantum Dots as Potent Membrane-Active Antibacterial Agents with Low Drug Resistance and Effective Inhibition of Biofilm Formation

Abstract: It is very challenging to design nanomaterials with both excellent antibacterial activity and cytocompatibility when facing bacterial infection. Here, inspired by antimicrobial peptides (AMPs), we fabricate carbon quantum dots (CQDs) derived from hydrophobic tryptophan and hydrophilic lysine or arginine (Lys/ Trp-CQDs and Arg/Trp-CQDs), which possess amphipathic properties. These CQDs could effectively destroy bacterial membranes without developing resistance, inhibit biofilms formed by Staphylococcus aureus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The antibacterial activity of Trp-CDs increased as the pH was reduced from 7.4 to 4.0 (Figure B), which might be partially due to the increased ζ potential of the surface of Trp-CDs under acidic conditions. Additionally, more positive charges might accelerate the contact process between the ultrasmall Trp-CDs and the bacterial cell membrane, , which could disrupt the structural integrity of the cell membrane and eventually lead to cytoplasmic leakage (Figure C). It was further confirmed that the surface charge of Trp-CDs played a vital role in determining their antibacterial potency.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of Trp-CDs increased as the pH was reduced from 7.4 to 4.0 (Figure B), which might be partially due to the increased ζ potential of the surface of Trp-CDs under acidic conditions. Additionally, more positive charges might accelerate the contact process between the ultrasmall Trp-CDs and the bacterial cell membrane, , which could disrupt the structural integrity of the cell membrane and eventually lead to cytoplasmic leakage (Figure C). It was further confirmed that the surface charge of Trp-CDs played a vital role in determining their antibacterial potency.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they proposed that CDs are not only an excellent electron donor (D), but also an excellent electron acceptor (A), which can transfer electrons with other A or D molecules [89]. Subsequently, numerous studies confirmed this conclusion [72,73].…”
Section: Photo-induced Electron Transfer Characteristicsmentioning
confidence: 99%
“…Based on the pyrolysis treatment of hydrophobic tryptophan and hydrophilic lysine or arginine, Li et al, developed amphipathic CDs using a simple method. These CDs destroy the bacterial membrane and rapidly kill bacteria via electrostatic interactions of cationic residues and the fusion of hydrophobic groups [73]. The amphiphilic CDs that were hydrothermally synthesized by Shaikh et al, using citrus as a raw material also inhibited bacterial adhesion and biofilm formation, while demonstrating a profound antibacterial activity [74].…”
Section: Amphiphilicitymentioning
confidence: 99%
“…Several CDs prepared from amino acids such as arginine [ 41 ], alanine [ 42 , 43 ], L-tryptophan [ 58 , 59 ], cysteine [ 43 , 44 ], lysine [ 59 ], and arginine [ 59 ] have been reported to possess antimicrobial activities. Suner et al synthesized nitrogen-doped arginine CDs (termed Arg CDs) utilizing citric acid as the carbon source and arginine as the amine source by a microwave-mediated approach ( Figure 2 B) [ 41 ].…”
Section: Antimicrobial Cdsmentioning
confidence: 99%